VOLUNTEERING AS A FORM OF SOCIAL PROTECTION - Khushnazarova Mamura Nodirovna (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the multifaceted role of volunteering as an active and dynamic form of social protection, the development of social stability, and the increase of community cohesion, as well as the role of volunteering in social life, are discussed.